Measurement and analysis of temperature dependent resistance of 𝑳𝒊𝒙𝑪𝒖0.5𝒁𝒏𝟎.𝟓−𝟐𝒙𝑭𝒆𝟐+𝒙𝑶4 - Jajayare, MD.Jabar Al (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2023.